Insights Into The Causes and Anti-hyperglycemic Effects Of Punica granatum Rind in Alloxan-induced Diabetic Rats - Sushil Kumar Middha (Science Faculty of Chiang Mai University, 2019)
In the present investigation, the anti-hyperglycemic potentialand scientific validation of Punica granatum rind/peel, a waste material and herbal drug,from Kumauni region was assessed in alloxan-induced diabetes model.The effectsof oral administration of different doses i.e low (LP) and high (HP) (LP; 75 mg/kg and HP; 150 mg/kg body weight) of methanolicfragment of P. granatumpeel(PGPE) on blood glucose, lipid peroxidation (MDA; malondialdehyde),antioxidant enzymes (SOD; superoxide dismutase and GPx; glutathione peroxidase) were estimated and compared with glibenclamide and insulin for 45 days.Treatment with PGPE, glibenclamide and insulin resulted in a significant reduction of blood glucoselevels as compared to solvent control (p<0.05).PGPEenhanced the plasma insulin level by five fold. PGPEalso resulted in a significant decrease in MDA values (p>0.001) in kidney (LP; 16.80 and HP; 52.08%) andan increase in antioxidants level (p>0.05) such as SOD 39.68% and 75.03%, GPx 20.07% and 67.60% in plasma and SOD 44% and 66%, GPx 50% and 80% inkidney, though MDA level was not significantly decreased(p<0.05) in plasma, when compared to diabetic controls.Histopathological studies also validated our studies of interest. To conclude, PGPE supplementation leads to an increase in insulin level in experimental animals, confirming restoration of pancreatic b-cells and other parameters clearly indicating the anti-hyperglycemic and antioxidant effect of PGPE.